Strategies of Bengkulu City Social Service in Distributing Social Assistance for Natural Disaster Victims - Romi Gustiandi Putra; Tuti Handayani; Yanuar Rikardo (Social Sciences Journal, 2026)
This study aims to determine and analyze the strategy of the Bengkulu City Social Service in distributing social assistance to natural disaster victims so that the assistance is accurate, efficient, and effective in Bengkulu City. This research uses a qualitative approach presented descriptively, with three informants selected for data collection through observation, interviews, and documentation. Based on the results of the research and discussion using the SWOT Analysis theory as the basis for organizational strategy preparation by Slamet Riyanto (2021:28), which consists of four indicators, the findings show that the Social Service has implemented a distribution strategy that is generally effective, yet still requires internal strengthening and optimal utilization of external opportunities to respond to various disaster risks sustainably. The results indicate that the Bengkulu City Social Service possesses strong institutional capacity, trained human resources, responsive procedures, and adaptive coordination, supported by clear SOPs that facilitate smooth distribution of disaster assistance. Limitations appear in budget constraints, irregular training, incomplete digital data systems, and less optimal internal communication. Significant opportunities arise from government policy support, cross sector collaboration, digital system development, and high community participation in disaster management. Various threats, including disaster uncertainty, political dynamics, physical barriers, and potential public complaints, have been addressed through preparedness efforts, standby logistics, and fast, humane service delivery.